Contact Pattern of Alveolar Consonants in the Malay Consonants of Paralysis Subject using Electropalatography - Mat Zin, Syatirah; M. Suhaimi, Fatanah; Md Shakur, Nur Fatehah; Mohd Noor, Siti Noor Fazliah; Mohamad, Ahmad Fakrul; Zali, Nurulakma (International Journal of Integrated Engineering, 2019)
Place of articulation plays an important part to produce different sounds. Besides the place of articulation, tongue is also an active articulator during a continuous speech. During the speech, the tongue moves around creating different sounds when it is placed at different place of articulation. The movement of tongue is controlled by muscles. The lack of muscle movement will produce inactive tongue movement. Paralysis is an example of the muscle weakness in a person resulting in difficulties to move. Paralysis may occur due to several factors including stroke and spinal cord injury (SCI). One of the indirect effects of paralysis is slurred speech and difficulty in speaking. This study aims to determine the contact pattern of five paralysed subjects during speech production of alveolar consonants in the Malay Language. The subjects had paralysis due to different aetiologies and with different medical history backgrounds. All participants were required to produce five single consonants; /d/, /t/, /l/, /n/ and /s/. The data recording was done in a studio laboratory with a soundproof system. The device used for detecting the tongue and hard palate contact in this study was electropalatography (EPG). Subjects were required to wear the artificial palate consists of 62 sensors to detect the tongue and hard palate contact. The speech contact was analysed using Articulate Assistant 1.18TM. The results were then compared with the average contact pattern of Malay speaker which had been obtained in the previous study. In conclusion, the subjects who had frequent treatments produced better articulation and the subjects with positive attitudes produced better articulation during the treatment process.